Cavitation and charge separation in laser-produced copper and carbon plasma in transverse magnetic field. (4th June 2021) - Behera, Narayan; Kumar, Ajai; Singh, R K
Abstract: In the present work, we report the dynamics and geometrical features of the plasma plume formed by the laser ablation of copper and graphite (carbon) targets in the presence of different transverse magnetic field. This work emphasizes on the effect of atomic mass of the plume species on the diamagnetic behaviour and geometrical aspect of the expanding plasma plume in the magnetic field. The time-resolved analysis of the simultaneously captured two directional images in orthogonal to the expansion axis is carried out for the comparative study of projected three-dimensional structure of copper and carbon plasma plume. In the presence of magnetic field, sharp differences are observed between the copper and carbon plasma plumes in terms of formation of diamagnetic cavity and structure formation. An elliptical cavity-like structure is observed in case of copper plasma plume which attains the sharp conical shape with increasing the time delay or magnetic field strength. On the other hand, splitted carbon plasma plume appears as a Y-shape structure in the presence of magnetic field where the cavity-like structure is not observed for the considered time and magnetic field. Based on the modified energy balance relation for the elliptic cylindrical geometry, we have also simulated the dynamics of the plume which is in close agreement with observed plasma expansion in diamagnetic and non-diamagnetic regions.